Genetic variants in N6-methyladenosine are associated with bladder cancer risk in the Chinese population - Liu, Hanting; Gu, Jingjing; Jin, Yu; Yuan, Qi; Ma, Gaoxiang; Du, Mulong; Ge, Yuqiu; Qin, Chao; Lv, Qiang; Fu, Guangbo; Wang, Meilin; Chu, Haiyan; et al. (Archives of toxicology, 2021)
Recently N 6 -Methyladenosine (m 6 A) has been identified to guide the interaction of RNA-binding protein hnRNP C and their target RNAs, which is termed as m 6 A-switches. We systematically investigated the association between genetic variants in m 6 A-switches and bladder cancer risk. A two-stage case–control study was performed to systematically calculate the association of single nucleotide polymorphisms (SNPs) in 2798 m 6 A-switches with bladder cancer risk in 3,997 subjects. A logistic regression model was used to assess the effects of SNPs on bladder cancer risk. A series of experiments were adopted to explore the role of genetic variants of m 6 A-switches. We identified that rs5746136 (G > A) of SOD2 in m 6 A-switches was significantly associated with the reduced risk of bladder cancer (additive model in discovery stage: OR = 0.80, 95% CI 0.69–0.93, P = 3.6 × 10 −3 ; validation stage: adjusted OR = 0.88, 95% CI 0.79–0.99, P = 3.0 × 10 −2 ; combined analysis: adjusted OR = 0.85, 95% CI 0.78–0.93, P = 4.0 × 10 −4 ). The mRNA level of SOD2 was remarkably lower in bladder cancer tissues than the paired adjacent samples. SNP rs5746136 may affect m 6 A modification and regulate SOD2 expression by guiding the binding of hnRNP C to SOD2, which played a critical tumor suppressor role in bladder cancer cells by promoting cell apoptosis and inhibiting proliferation, migration and invasion. In conclusion, our findings suggest the important role of genetic variants in m 6 A modification. SOD2 polymorphisms may influence the expression of SOD2 via an m 6 A-hnRNP C-dependent mechanism and be promising predictors of bladder cancer risk.